Efficient Bioelectrochemical Cell Generation and Green Synthesis of Silver Nanoparticles Using Pomegranate and Pineapple Peel Extracts: A Comprehensive Characterization Study - Mehrin, Shamima; Tanisa, Nilufer Yesmin; Awal, Rabiul; Alam Khan, Md. Kamrul; Shaqur, Abdus; Ahmed, Shamim; Islam, Shahidul; Mia, Asad (Advances in materials science and engineering, 2024)
The present study investigates an environmentally conscious method for synthesizing silver nanoparticles (AgNPs) by employing extracts from pomegranate peel (PgP) and pineapple peel (PnP). This green synthesis approach offers a sustainable alternative to traditional chemical methods, thereby reducing the ecological footprint associated with nanoparticle production. The PgP and PnP extracts serve as both reducing and capping agents during the synthesis process, enhancing the biocompatibility of the resultant AgNPs. Various characterization techniques, including UV-Vis spectroscopy, Raman analysis, X-ray diffraction (XRD), dynamic light scattering (DLS), Fourier transform infrared (FTIR), and transmission electron microscopy (TEM), were utilized to analyze the synthesized AgNPs. UV-Vis spectroscopy confirmed the formation of AgNPs through characteristic surface plasmon resonance peaks, while FTIR examined the interaction between biomaterial components and the oxidation and coating of silver nanoparticles. Raman analysis elucidated the functional groups responsible for reducing and stabilizing AgNPs, while XRD provided insights into their crystalline structure. TEM images revealed the size and morphology of the nanoparticles, while DLS characterized their average size and morphology. In addition, the synthesized AgNPs were utilized in a bioelectrochemical cell to leverage their unique properties for enhanced electrochemical performance, showcasing their potential application in energy storage and conversion systems. Overall, this study demonstrates the feasibility of utilizing agricultural waste products such as PgP and PnP for sustainable AgNP synthesis, offering promising prospects for environmentally friendly nanotechnology advancement.